The Nuremberg Trial: Procedural Due Process at the International Military Tribunal - McKeown, Tessa (Victoria University of Wellington Law Review, 2014)
For over 60 years, lawyers and historians have discussed the credibility and repercussions of the Nuremberg Trial (1945–1946). The Nuremberg Trial at the International Military Tribunal was conducted by the four Allied Powers to try the upper echelon Nazi war criminals following the Second World War. The London Charter, drafted by the Allies, outlined the trial procedure to be adopted, and provided certain guarantees in an attempt to secure a fair trial for the 22 defendants. This article examines the history of fundamental due process rights (recognised in both Continental Europe and Common Law jurisdictions) and analyses the extent to which these rights were breached at Nuremberg. It argues that the defendants’ procedural due process rights were partially protected at Nuremberg, although there were gross breaches of particular fundamental due process rights. This article further argues that despite the defendants being afforded more rights than they could have expected given the circumstances, such breaches significantly compromised the integrity of the trial.